The shadow and the sea: Management and recovery of an abandoned public space in Chimbote, Peru - Montestruque Bisso, Octavio (2022)
Architecture, however modest, must meet the basic needs of habitability and dignify the life of the human being. In that sense, shadows in the public space becomes a fundamental element to be able to allow its occupation and, with it, to generate the benefits and potentialities of coexistence in community. This article presents the Tetra experimental structure in the city of Chimbote as an example of a punctual and modest intervention that, through the work of professionals, students and community members, manages to activate an abandoned and at risk public space thanks to a correct understanding of the needs and potentialities of the landscape.